Aplikasi Penyesuaian Stock Sebagai Pendukung Proses Audit Pada Perusahaan Manufaktur dengan Metode RAD - Ralfpiere Charlitos; Steffi Adam (J-INTECH ( Journal of Information and Technology), 2023)
XYZ is one of many manufacturing companies in the city of Batam operating in the field of plastic injection molding attempting to improve their business process by creating and integrating an information processing system. Currently, PT. XYZ is facing an issue regarding inaccuracy between physical and digital stock. This issue caused PT. XYZ to miss an opportunity to appeal towards a larger market. Despite doing an inventory audit, the inhouse system owned by the company didn’t accommodate input of the audit result regarding the stocks real condition, thus causing a need for time to figure out the root cause of a stock inaccuracy issue and to also solve it. This research is done to develop an application using a short and fast development cycle and implementation to receive results quicker with the intention of allowing the company to make a decision. The method used in Rapid Application Development (RAD), contains 3 processes which consists of, Requirements Planning, Design and Implementation. The result of the research shows that implementation of this system speeds up the investigation process of stock inaccuracy so that the company could deal with issue at hand immediately. Furthermore, according to observation results, the accuracy of the data between the system and the actual achieved 90%, which is an increase of around 30-40% compared to before the system was implemented